Effect of Including Fermented Feather Meal as Substitution of Concentrate in the Basal Diet With Different Levels on the Performance of Landrace Crossbred Pigs - N. S. Dalle; S. Sembiring; E. J. L. Lazarus (Jurnal Sain Peternakan Indonesia, 2022)
The study aimed to evaluate the effect of adding fermented feather mael (FFM) on pigs' performance, intake, and digestibility. There were 16 landrace crossbred pigs 2-3 months old with 6-19 kg (average 13.59 kg; CV= 29.59%) initial body weights used in the study. Trial method using complete block design 4 treatments with 4 replicates procedure was applied in the study. The 4 treatment feeds were formulated as: R0: basal diet with 100% concentrate without TBAT (control); R1: basal diet with 90% concentrate + 10% FFM; R2: basal diet with 80% concentrate + 20% FFM; and R3: basal diet with 70% concentrate + 30% FFM. Variables evaluated were feed intake, daily weight gain and feed conversion (performance) landrace crossbred pigs. Statistical analysis shows no significant (P>0.05) on feed intake, daily weight gain and feed conversion. The conclusion were that that including FFM into basal diet gave relative the same results in the feed intake, daily weight gain and feed conversion.